Enhancement of Hybrid Solar Air Conditioning System using a New Control Strategy - Mohammed, Ahmed Abed; Abduljabbar, Raed Ayad (Al-Khwarizmi Engineering Journal, 2018)
Enhancement of the performance for hybrid solar air conditioning system was presented in this paper. The refrigerant temperature leaving the condenser was controlled using three-way valve, this valve was installed after the compressor to regulate refrigerant flow rate towards the solar system. A control system using data logger, sensors and computer was proposed to set the opening valve ratio. The function of control program using LabVIEW software is to obtain a minimum refrigerant temperature from the condenser outlet to enhance the overall COP of the unit by increasing the degree of subcooled refrigerant. A variable load electrical heater with coiled pipe was used instead of the solar collector and the storage tank to simulate the solar radiation.  Experimental data was measured to study the performance of the system. The proposed system was compared with the conventional one. Results show that the COP of the proposed system was higher than the COP of the conventional system by 10 %. In addition, the controlled system saved an electricity of 11.2 %. The optimum opening valve ratio fluctuated between 0.3 and 0.4 when the heater power was 500 W.